Improving oil extraction efficiency in wells complicated by mechanical impurities using simultaneous-separate exploitation technology - Pugach I. O. (НТУ «ДП», 2025)
Mechanical impurities pose significant challenges in oil extraction, particularly in multilayer reservoirs with horizontal wells. These impurities, including dispersed rock particles, corrosion products, asphaltene-resin-paraffin deposits (ARPD), and mineral salts, lead to equipment failures, reduced flow rates by 20-50%, and increased repair costs up to 30-40% of operational expenses. In early-stage development (fund realization <2%), with impurity concentrations up to 1000 mg/L, traditional methods are inefficient due to near-wellbore zone (NWZ) destruction under depression. This study investigates simultaneous-separate exploitation (SSE) technology integrated with combined impurity control methods to enhance extraction efficiency in such complicated wells [1, 2]. Mechanical impurities originate from four main sources: the reservoir (rock destruction products and proppant from hydraulic fracturing), process fluids (poorly filtered killing fluids, flushing liquids, and reagents), equipment (corrosion products and metal salts), and debris (from drilling, repairs, and perforations, including cement crusts, rubber fragments, and mud). Even short stops (15-20 minutes) cause sedimentation, jamming plungers in rod pumps or clogging impellers in electric submersible pumps (ESPs), inducing vibrations and failures. High-impurity bursts (>500 mg/L) reduce equipment lifespan by 1.5-2 times [3, 4].
Keywords: видобуток нафти; експлуатація свердловин